ANALISIS PENGARUH INSTRUMEN PEMBAYARAN NON-TUNAI TERHADAP STABILITAS SISTEM KEUANGAN DI INDONESIA - Lintangsari, Nastiti Ninda; Hidayati, Nisaulfathona; Purnamasari, Yeni; Carolina, Hilda; Ramadhan, Wiangga Febranto (JURNAL DINAMIKA EKONOMI PEMBANGUNAN, 2018)
The payment system is an important component in the economy especially to ensure the implementation of payment transactions made by the public and the business world. In addition, the payment system also plays an important role in supporting financial system stability and implementation of monetary policy. Along with rapid technological developments, patterns and payment systems in economic transactions are constantly changing. Technological advances in the payment instruments shift the role of cash as a means of payment in the form of more efficient and economical non-cash payments. Non-cash payment instruments used in this study are card-based payment instruments (APMK) and electronic money (e-money). The aim of this study is to examine the effect of non-cash payment instruments development on money supply (M1), velocity of money, inflation, interest rate, and financial system stability. A set of secondary data are assessed through official website of Bank Indonesia from year 2009-2017. Multiple regression analysis are employed to elaborate the results. The result showed that e-money and credit card transactions have a significant positive effect on M1, e-money transactions have a significant negative effect on interest rates, and credit card transactions have a significant positive effect on interest rates.